Openness, exchange rate regimes and the Phillips curve. - Bowdler, C (Nuffield College (University of Oxford), 2005)
A number of theoretical models predict that the slope of the Phillips curve increases with trade openness, but cross-country studies provide little evidence for such a correlation. We highlight two reasons for this …finding. Firstly, the strength of the relationship may depend on the extent of exchange rate adjustment, which is a potential determinant of output and inflation dynamics in open economies, but previous studies have not made a distinction between …fixed and floating exchange rate regimes. Secondly, existing estimates of the Phillips curve slope are based on data from the 1950s through the 1980s, and are therefore likely affected by price and wage controls, inflationary oil price hikes and the role played by …fiscal policy in driving output and inflation (the underlying theory requires that monetary shocks dominate). We calculate new measures of the Phillips curve slope using data from 1981-98, a period during which these factors were arguably less important. Regressions based on the new measures indicate that the Phillips curve slope increases with trade openness amongst countries maintaining flexible and semi-flexible exchange rate regimes, but is unrelated to openness amongst countries maintaining …fixed exchange rate regimes.